Degradation characteristics of two typical N-heterocycles in ozone process: Efficacy, kinetics, pathways, toxicity and its application to real biologically pretreated coal gasification wastewater. (October 2018) - Zhu, Hao; Ma, Wencheng; Han, Hongjun; Xu, Chunyan; Han, Yuxing; Ma, Weiwei
Abstract: Ozonation of pyridine and indole was investigated both in aqueous solution and biologically pretreated coal gasification wastewater (BPCGW). Experimental results showed that the removal of indole was hardly affected by pH value. Direct reaction rate constant of ozone with pyridine increased from 0.18 M −1  s −1 (protonated pyridine) to 3.03 M −1  s −1 (molecular pyridine), and that with molecular indole was 8.6 × 10 5  M −1  s −1 . Seven and five transformation intermediates were observed for pyridine and indole, respectively. Ozonation pathways were proposed as hydroxylation, opening and cleavage of the aromatic ring. It was found that ammonia nitrogen (NH3 N) increased by 3.3 mg L −1 in ozone process, suggesting the broken of the CN bonds of pyridine, indole and other N-heterocyclic compounds. In terms of biochemical oxygen demand to chemical oxygen demand (BOD5 /COD), toxicity and resazurin dehydrogenase activity (DHA), the biodegradability was improved after ozone treatment, indicating the possibility of ozone combined with biosystem for the treatment of BPCGW. The results of gas chromatograph and mass spectrometry (GC-MS) indicated that primary products during first 10 min might lead to the obstinate toxicity, which was further proved by US Environmental Protection Agency (US-EPA) test. This study would assist in obtaining a better understanding of the application of ozonation pretreatment in BPCGW. Graphical abstract: Image 1 Highlights: The removal of indole was hardly affected by pH value. The reaction rate constants of ozone with pyridine and indole were calculated. Seven and five intermediates were found for pyridine and indole in ozone process. Primary products during first 10 min might lead to the obstinate toxicity.